2017
DOI: 10.1186/s13756-016-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the WHO multimodal Hand Hygiene Improvement Strategy in a University Hospital in Central Ethiopia

Abstract: BackgroundThe burden of health-care associated infections in low-income countries is high. Adequate hand hygiene is considered the most effective measure to reduce the transmission of nosocomial pathogens. We aimed to assess compliance with hand hygiene and perception and knowledge about hand hygiene before and after the implementation of a multimodal hand hygiene campaign designed by the World Health Organization.MethodsThe study was carried out at Asella Teaching Hospital, a university hospital and referral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 26 publications
9
57
3
Order By: Relevance
“…Among the disinfectants (e.g. aldehyde, halogen-releasing agents, phenols), alcohols are the most used due to their good effectiveness, low cost and availability, especially in less developed countries (5,6). Although several alcohols have been considered to have antimicrobial effects, only three of them are widely used, namely ethyl alcohol -ethanol, isopropyl alcohol -isopropanol (or propan-2-ol), and n-propyl alcohol -n-propanol (or propan-1-ol) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Among the disinfectants (e.g. aldehyde, halogen-releasing agents, phenols), alcohols are the most used due to their good effectiveness, low cost and availability, especially in less developed countries (5,6). Although several alcohols have been considered to have antimicrobial effects, only three of them are widely used, namely ethyl alcohol -ethanol, isopropyl alcohol -isopropanol (or propan-2-ol), and n-propyl alcohol -n-propanol (or propan-1-ol) (7).…”
Section: Introductionmentioning
confidence: 99%
“…PASQUALE baseline and follow-up assessments found better overall results than studies conducted in university hospitals in comparable settings such as Mali and Ethiopia [11,12]. space and belongings are often shared [11].…”
Section: Discussionmentioning
confidence: 76%
“…Low hand hygiene practices is common in other countries in Africa and Asia as reported in other countries, the main reason being lack of knowledge on how proper hand hygiene is practiced, sensitisation and lack of ABHR for hand decontamination. 15,[23][24][25] High workload and facility ownership are additional factors linked with low compliances of hand hygiene as reported by studies in India and China, where low compliance of hand hygiene was noted more frequently in public compared to private facilities. [26][27][28] Although an improvement in hand hygiene compliance was observed in the current study, little improvement was observed in washing hands with water or ABHR for at least 2 minutes and wearing sterile gloves correctly before procedure.…”
Section: Discussionmentioning
confidence: 95%